ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI ATAS PENGAJUAN DAN PEMBAYARAN KLAIM ASURANSI PESERTA PENSIUN PADA PT ASABRI (PERSERO) JAKARTA - Oktavia Monita Asri, (2020)
The purpose of this study was to determine the application of accounting information systems in the filing and payment of retirement claims at PT ASABRI which conducts business processes in the insurance field for participants of TNI Soldiers, Porli Members, Civil Servants, Ministry of Defense, BUMN, BUMD which relate to elements of the information system accounting. The method in this study is a qualitative method with the approach of ethnometodology and interpretative paradigm. The results obtained from the study show that the procedure for submitting and paying pension claims is in accordance with the SOP, the Pension Fund Management System Using the "Pay as you go" System and the PT ASABRI Accounting Information System are running well and effectively, In Retirement Pension Funds using 3 ways namely: Come directly to the Pay Partner, ATM, Power of Attorney and Legacy Letter. But it is necessary to Monitoring Human Resources in operating Axapta for the sustainability of the system.